Turn – Taking Organized by the Host and Guests in “Let Them Speak” Talkshow Broadcast on First Channel Russia TV in 5th December 2014 - Liliek Soepriatmadji (Universitas Stikubank (UNISBANK) Semarang, 2015)
This paper is aimed at construing the turn-taking system organized by the host and guests in Let them speak talkshow which was broadcast on First Channel Russia TV in December 5th, 2014. The results indicate that the speakers tend to employ the turns in terms of sentences (114 units). The speakers managed their turns by selecting a different speaker (47 units), continuing one’s own turn (75 units), and selecting the next speaker him/herself (29 units). With respect to turn-taking strategy, the speaker tend to employ clean start (16 units), uptake (33 units), link (11 units), alert (10 units), meta-comment (16 units), and new start (12 units). The analyzed data also reveals that some participants seem to properly organize their turns dominantly in sentences, by employing next speaker self-select technique, and in clean starts, uptakes, and meta-comments. Key words: turn-taking system, turn, turn-taking strategy, clean start, uptake, meta-comment